Analysis Landslide Hazard in Banjarmangu Sub District, Banjarnegara District - Priyono, Kuswaji Dwi; Priyana, Yuli; Priyono, Priyono (Universitas Muhammadiyah Surakarta, 2006)
The objective of the research is to find the most suitable soil conservation practice that may be applied to control landslide hazard. In order to achieve that objective, some research steps must be done, are: (1) to identify the land characteristics of the study area that is based on the understanding of some factors that caused and triggered the landslide hazard, i.e.: slope morphology, rocks/soils characteristics, climatic condition, and landuse; (2) to study the types of landslide that occurs in every landforms and determine the area having ideal landslide form; The proposed landslide in this research is the process of masswasting down-slope as a result of the gravitation action on materials being sliding. The landslide types is including creep, slide, slump, and rocks/soils fall. The methods that being applied in the research include field survey methods and the method for determining landslide hazard by using geographic information techniques. Field survey method was intended to characterize the location of every landslide that have been happened in the study area. The results of field survey were applied as materials for determinating the grade of landslide hazard. Scorring and weighting methods of factors that influence landslide was apllied to determine the grade of landslide hazard. Scor and weight were not same for every parameters used for evaluation. The result of field research shows that landslide happen in every landform unit The study area can be devided into 9 landform unit. The landform units are differentiated into the landslide hazard classes, the study area there were found 5 classes of landslide hazard, namely: (1) vary low hazard equal to 16,65% (1 landform unit); (2) low hazard equal to 7,63% (1 landform unit); (3) medium hazard equal to 37,58% (3 landform unit); (4) high hazard equal to 25,41% (2 landforms unit); and (5) highest hazard equal to 12,73% (2 landform unit). Evaluation of landslide hazard shows hat most of study area have high risk to slide as a result of complex interaction between many factors of landslide.